Lay Evaluations of Restraints and Prohibitions During the 1st, 2nd, and 4th Wave of the COVID-19 Pandemic in Lithuania - Valickas, Gintautas; Vanagaitė, Kristina; Švedas, Gintaras (Teisė, 2023)
The article analyzes how, during the separate waves (the 1st, 2nd, and the 4th) of the coronavirus pandemic, participants of a study (overall n = 1356) assessed the government-imposed restrictions, prohibitions, liabilities and penalties for non-compliance with said restrictions, the perceived fairness of the behavior of other people during the pandemic, and the changes of their assessments during the coronavirus pandemic. Obtained evidence suggests that during the Covid-19 pandemic (from the 1st to the 4th wave) the participants of the study assessed the non-compliance with restrictions and prohibitions more and more forgivingly.